MbedML: A Machine Learning Project for Embedded Systems - Estrebou, César Armando (2021)
This article describes the tasks being carried out within the framework of a research and development project on machine learning techniques and algorithms applied to small devices. It includes a brief review of the available technologies, online development platforms, work methodology and open source software for the implementation of solutions. Experiments carried out on a proper implementation of an inference algorithm for convolutional neural networks are also presented with interesting preliminary results regarding existing implementations.